ARSIP SEBAGAI PENDUKUNG PEMAJUAN KEBUDAYAAN DALAM KONTEKS PEMBANGUNAN LITERASI BANGSA: Array - Toto Widyarsono (Arsip Nasional Republik Indonesia, 2017)
Cultural heritages have to be preserved and at the same time they need to be used properly in order to seek a new form to maintain their existence in this modern world. It is one of a challenge in the globalization era that needs to be overcome positively. Creative innovation is needed so that these cultural heritages would not be forgotten. The cultural heritages should be in a new form in order to maintain their existence. The combination between tradition and creativity will create new superior things. One of the cultural heritages is archive. Archive consists of a media of recording that contains documented information. Besides that, archive holds a record of the journey of a nation and has valuable contribution to develop the national literacy rate.